Time Consumption and Productivity of Sandat Felling Technique in Agroforestry Private Forests in Probolinggo, Indonesia - Budiaman, Ahmad; Hardjanto; Agustin, Sarah; Lawrensia; Rahayaan, Yohana Natalia; Maharani, Chandra Puspita; Limbong, Zest (Institut Pertanian Bogor (IPB University), 2024)
Agroforestry is a cropping pattern that is commonly applied to private forest management in Indonesia. Agroforestry based private forest is a land-based silviculture that incorporates forestry plants with agricultural crops, plantation crops, and multi-purpose plants. One of the felling techniques used in agroforestry based private forests is the sandat-felling technique (SFT), which is a rope-assist felling technique. The felling technique was used to protect the remaining stand of the agroforestry based private forest. This technique is an innovation in the harvesting of agroforestry based private forests in Indonesia. The time consumption and productivity of this technique are not yet known. This study aims to assess the working time and productivity of SFT in agroforestry based private forests in Probolinggo, East Java, Indonesia. The observed tree-felling technique included rope installation and tree-felling operations. The performance of the SFT was evaluated by analyzing its working time and productivity. The results of the study showed that the total working time of the SFT was 8.65 minutes tree-1, which consisted of 33.34% for rope installation and 66.66% for felling operation. The productivity of the SFT was 2.02 m3 hour-1.